Formulasi dan Uji Aktivitas Anti-aging Sediaan Hand Cream yang Mengandung Ekstrak Etanol Kulit Buah Nanas (Ananas comosus (L.) Merr.) - Sumaiyah; Gulo, Jevon Three Kartika (Talenta Publisher, 2024)
Hand skin that is often exposed to the sun easily loses moisture and is more rough. Hand cream is a care product that is applied to the palms and backs of the hands that can help restore hydration and skin function due to dry and rough skin. Pineapple peel contains flavonoids, vitamin C, and bromelain enzymes that has potential to be formulated into anti-aging preparations. This research aims to formulate ethanol extract of pineapple peel (Ananas comosus (L.) Merr.) into hand cream and to test the effectiveness as anti-aging agent. This research included making extracts by percolation method using 70% ethanol solvent, testing the antioxidant activity of pineapple peel extract using DPPH method, and hand cream formulations with the addition of pineapple peel extract with respective concentration of 0% (F0), 5% (F1), 7.5% (F2), and 10% (F3). Evaluation of hand cream preparations included organoleptic test, homogeneity, emulsion type, pH, viscosity, and physical stability at room temperature storage for 12 weeks and cycling test. Anti-aging effectiveness testing was carried out during the 4 weeks treatment period, by measuring parameters such as moisture, pores, blemishes and wrinkles on the skin of the backs of volunteers' hands which were measured once a week using a skin analyzer. The results of the antioxidant activity test of the ethanol extract of pineapple peel were included in the strong category with an IC50 value of 88.21 Âµg/mL. The hand cream preparation produced was homogeneous, O/W emulsion type, pH value 5.09-6.56, viscosity value 4086.76-6104.96 cPs, stable during 12 weeks of storage at room temperature and stable in the cycling test for 4 weeks. Hand cream preparations with a concentration of 10% have better effectiveness than 0%, 5% and 7.5% which results in an average percent moisture recovery of 77.60%, pores 62.92%, blemishes 55.65%, and wrinkles 45.92%.